Readiness of Parents in Utilizing Information and Communication Technology (ICT) in Children's Learning during the Covid-19 Pandemic - Lestari, Gunarti Dwi; Yulianingsih, Wiwin; Widodo, Widodo; Widyaswari, Monica (Universitas Negeri Semarang, 2022)
This study aims to determine parents' readiness to use ICT in children's learning during the Covid-19 pandemic. This study used quantitative research. The population in this study amounted to 571 respondents, while the sample in this study obtained many 230 respondents with research subjects, namely parents who have school-age children (students from PAUD/SD/SMP/SMA levels and currently implementing online learning). The sampling technique used is the purposive sampling technique. The data analysis technique in this study used descriptive statistical techniques. The study's overall results show that the readiness of parents in the use of ICT in children's learning during the Covid-19 pandemic shows good results with a percentage of 76.09%. These results are supported by the suitability of the results for each sub-variable, namely the sub-variables of parental readiness and ICT use in online learning. In this case, it can be interpreted that an educator must have readiness and understanding of the online learning system, but parents must also understand and master the technical implementation of online learning.